Novel ABA–type Block Copolymers from Telechelic PEG–initiated Hydrogen–transfer Polymerization. Issue 2 (3rd April 2022) - Çatıker, Efkan; Atakay, Mehmet; Salih, Bekir
ABSTRACT: Novel ABA-type block copolymers were prepared using end-groups activated poly(ethylene glycol) (PEG) as an initiator for hydrogen transfer polymerization (HTP). For this purpose, PEG with average molar mass of 1450 Da (PEG-1450) was firstly treated with the equivalent amount of sodium hydride to synthesize PEG with dialkoxide end-groups, namely PEG-dialkoxide. Using the PEG-dialkoxide as a macroinitiator, base-catalyzed HTP of acrylamide, N -methoxypropyl acrylamide, and 2-hydroxyethyl acrylate were then performed to achieve the novel ABA-type block copolymers. The copolymers were obtained with high yields of about 90%. Characterization of the ABA-type copolymers was carried out using Fourier Transform Infrared Spectroscopy (FTIR spectroscopy) and Matrix Assisted Laser Desorption Ioizaton (MALDI) mass spectrometry. FTIR spectra of the copolymers exhibited some characteristic bands assigned to the functional groups arising from the mechanism of HTP. Molar mass distributions of the copolymers from the MALDI mass study pointed out that chain extensions by mass in each copolymer were almost equal. Hence, the MALDI mass spectra of the copolymers revealed that chain extensions of telechelic PEGs by β-alanine, 2-hydroxyethyl acrylate, and N -methoxypropyl β-alanine units were successfully fulfilled.